Spol in besedni red v dvoimenskih prirednih zvezah - Perko, Gregor (Slavistična revija, 2019)
The article focuses on binominals with masculine and feminine nouns denoting humans linked by the conjunction in (and). I attempt to highlight the complexity of the reasons that influence word order in these binominals.
Keywords: discourse; diskurz; gender; morphology; morphosyntactic categories; oblikoslovje; oblikoslovnoskladenjske kategorije; pragmatics; pragmatika; semantics; semantika; spol